The identification of microRNAS Pathogenic pathway in acute Myocardial Infarction of young adults - Abdullah, Nor Zamzila; Muhammad Musa, Nurul Ashikin; A Talib, Noorlelawati; Abdullah, Aszrin; Mohd Shah, Azarisman Shah; Muhammad, Siti Aeshah @ Naznin (2023)
Acute myocardial infarction (AMI) is a severe form of coronary heart disease where Malaysians are getting AMI at younger age compared to well-developed countries. MicroRNAs (miRNAs) are implicated in AMI pathogenesis, but no study looked at their profiling or involvement in young population. The present study aims to profile the miRNAs expressions in healthy controls (aged 18 to 45 years), young AMI (YAMI) (aged ≤ 45 years), and mature AMI (MAMI) (aged ≥ 46 years) patients with matching criteria, and to determine the effect of the dysregulated miRNAs on the target mRNAs as well as the pathways involve in the pathogenesis of AMI. This study was conducted on twenty Malay males for each group in Kuantan, Pahang. Total RNA was extracted from plasma and the miRNA expression profiling was carried out on the BGISEQ500 SE50 sequencing platform with BGI sequencing libraries. The sequence data were analyzed using Gene Ontology (GO) to determine the role of the differentially expressed genes, followed by the Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis for identification of the biological pathways in YAMI against MAMI. The top six dysregulated miRNAs identified during sequencing were validated using quantitative reverse-transcription polymerase chain reaction (qRT-PCR) between the groups. ANOVA and unpaired T-test were used to analyze the differences of miRNAs and gene expression between the three groups. This study revealed that majority AMI patients were smokers, where YAMI patients had higher BMI, SBP, DBP and TG while MAMI patients had higher FBG than the rest of the group. A total of 1599 miRNAs were differentially expressed in AMI (YAMI and MAMI) patients compared to healthy controls, where 1288 were upregulated and 311 were downregulated (FDR ≤ 0.001). However, when YAMI patients were compared to MAMI patients, 1497 miRNAs were found to be dysregulated, of which 1090 miRNAs were upregulated, and 407 miRNAs were downregulated (FDR ≤ 0.001). The top ten upregulated miRNAs were miR-552, miR-4446-3p, miR-432-5p, miR-548j-5p, miR-219, miR-982, miR-181a-2-3p, miR-654-5p, miR-58 and miR-548k; while the top ten downregulated were miR-16-5p, miR-1064, miR-431-5p, miR-790 miR-1177, miR-201, miR-105, miR-518, miR-419 and miR-1103. This study also discovered ten novel miRNAs: miR-4446-3p, miR-982, miR-58, miR-548k, miR-1064, miR-790, miR-1177, miR-201, miR-419, and miR-1103. The validation of the top six dysregulated miRNAs between YAMI and MAMI patients revealed the upregulation of miR-423-5p by 2.08-fold (p = 0.040) and downregulation of miR-431-5p by 33.90-fold (p = 0.034), and miR-378a-5p by 34.61-fold (p = 0.040). For these 1497 differentially expressed miRNAs, 34,195 target genes were predicted by GO analysis. The functional analysis demonstrated 11,199 GO terms found to be involved in biological processes, 12,012 in cellular components, and 10,984 in molecular functions were significantly enriched (p < 0.05). The target genes that were mapped to the signal transduction pathway in KEGG revealed 346 classes were enriched. In conclusion, miRNAs are differentially expressed between young and mature AMI, ten of which are novel. Three biological pathways, ascorbate and aldarate metabolism, collecting duct acid secretion and glycosaminoglycans biosynthesis – heparin sulfate/heparin were identified but their involvements in the regulatory mechanisms on gene expression in Young AMI need further evaluation.